The Developmental Role of Social Work in Reducing Social Extremism:A Field Study in Baghdad University-College of Mass Communication as a Model: محمد حميد علوان (Journal of the College of Education for Women, 2021)
This study deals with the role that social work profession plays in all its fields to reduce social extremismat home, or school or within society. The study aims to: examine the historical roots of social work in the Iraqi society, investigate the objectives of the developmental role of social work, review the theories of social extremism, its characteristics, and causes, and to analyze the developmental role of social work to limit social extremism. To meet the objectives of the study, a descriptive analytical approach has been adopted. It involves using the social sampling survey method, i.e., a questionnaire tool in the University of Baghdad community-College of Media. The sample was randomly selected to include (100) students from the College of Mass Communication. The study has concluded that (75%) of the sample answered Yes about the developmental role of social work in curbing extremism within the family. Moreover, 85% of the research sample emphasized the developmental role of social work in curbing extremism within the school community. The results have also revealed a relationship between the developmental role of social work and the reduction of social extremism within the school community. This is because the computed value is (68.5) which is greater than the tabulated value (48.3) at a degree of freedom (1) and a level of significance (0.05). It has alsobeen noted that there is a significant correlation relationship at (0.05) level of significance between the developmental role of social work and social extremism.